Political risk and the Iceland : UK interconnector : risk mitigation, ownership and dispute settlement - Andri Dan Traustason 1992- (2016)
Verkefnið er lokað til 1.6.2016. The proposed interconnector between Iceland and the United Kingdom carries numerous different types of risk for Iceland. Ownership of the interconnector and the infrastructure related to it needs to be settled in a way that minimizes political risk for the Icelandic nation without sacrificing national sovereignty over its renewable energy sources. A public-private partnership project could use various methods to mitigate risk, many of which are related to ownership and financing. Guarantees and loans provided by IFIs, such as the European Investment Bank and the Nordic Investment Bank, might play a fundamental role in that regard. Export credit agencies might also provide political risk insurance. Other solutions, such as a bilateral legal agreement and contracts for difference, will also be assessed with regard to the interconnector. In the event of disputes occurring, the Energy Charter organization and ICSID, of the World Bank, might be key players among other institutions. These solutions would require serious arbitration provisions and awards would be subject to the New York Convention. Sæstrengur milli Íslands og Bretlands felur í sér ýmsar tegundir áhættu fyrir Ísland. Pólitísk áhætta vegur þungt þrátt fyrir að oft sé horft fram hjá henni í rannsóknum á fýsileika verkefnisins. Eignarhald og fjármögnun verkefnisins getur haft veruleg áhrif í þessu tilliti og nauðsynlegt er að finna lausn sem lágmarkar pólitíska áhættu án þess að fórna yfirráðum yfir verðmætum endurnýtanlegum náttúruauðlindum. Einkaframkvæmdir (samstarfsverkefni opinberra aðila og einkaaðila, e. PPP) innlendra og erlendra aðila gætu verið hluti af verkefninu og nýtt sér ýmsar leiðir til áhættustýringar sem margar hverjar tengjast fjármögnun og eignarhaldi. Tryggingar og lán frá alþjóðafjármálastofnunum, svo sem Fjárfestingarbanka Evrópu (EIB) og Norræna Fjárfestingarbankanum (NIB), gætu spilað lykilhlutverk þar að lútandi. Export credit agencies (stundum kallaðar tryggingadeildir útflutnings) gætu einnig ...